Biocrust‐forming mosses mitigate the impact of aridity on soil microbial communities in drylands: observational evidence from three continents. Issue 3 (2nd April 2018) - Delgado‐Baquerizo, Manuel; Maestre, Fernando T.; Eldridge, David J.; Bowker, Matthew A.; Jeffries, Thomas C.; Singh, Brajesh K.
Summary: Recent research indicates that increased aridity linked to climate change will reduce the diversity of soil microbial communities and shift their community composition in drylands, Earth's largest biome. However, we lack both a theoretical framework and solid empirical evidence of how important biotic components from drylands, such as biocrust‐forming mosses, will regulate the responses of microbial communities to expected increases in aridity with climate change. Here we report results from a cross‐continental (North America, Europe and Australia) survey of 39 locations from arid to humid ecosystems, where we evaluated how biocrust‐forming mosses regulate the relationship between aridity and the community composition and diversity of soil bacteria and fungi in dryland ecosystems. Increasing aridity was negatively related to the richness of fungi, and either positively or negatively related to the relative abundance of selected microbial phyla, when biocrust‐forming mosses were absent. Conversely, we found an overall lack of relationship between aridity and the relative abundance and richness of microbial communities under biocrust‐forming mosses. Our results suggest that biocrust‐forming mosses mitigate the impact of aridity on the community composition of globally distributed microbial taxa, and the diversity of fungi. They emphasize the importance of maintaining biocrusts as a sanctuary for soil microbes in drylands.